DEVELOPMENT OF VISUAL–IMAGINAL THINKING IN PRESCHOOL CHILDREN THROUGH ORGANIZED ACTIVITIES IN DEVELOPMENT CENTERS (Eureka Journal of Education & Learning Technologies, 2026)
This article explores the pedagogical and psychological foundations of effectively organizing the activities of development centers in fostering visual–imaginal thinking in preschool children. It also examines the methodological possibilities for organizing educational activities within development centers and develops practical recommendations based on the scientific views of both foreign and local scholars. The research findings indicate that development centers constitute an effective pedagogical environment for enhancing the imaginal form of thinking in children.
Keywords: Development Centers, Visual–Imaginal Thinking, Preschool Education, Game-Based Technology, Cognitive Development, Pedagogical Environment.